2019
DOI: 10.1177/0899764019848492
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Community Service: Self-Selection and the Effects of Participation

Abstract: Numerous studies demonstrate the effectiveness of university-based community service programs on students’ personal, social, ethical, and academic domains. These effects depend on both, the characteristics of students enrolled and the characteristics of the programs, for instance whether they are voluntary or mandatory. Our study investigates whether effects of voluntary service programs are indeed caused by the service experience or by prior self-selection. Using data from a pre–post quasi-experimental design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 77 publications
0
15
1
4
Order By: Relevance
“…Howard (1993) focused on students learning responsibility and addressing meaningful issues, while Speck and Hoppe (2004) made civic engagement and communitarian involvement primary. Studies have affirmed the long-term positive effects of service-learning programs for students' personal, academic, and moral development (Meyer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Howard (1993) focused on students learning responsibility and addressing meaningful issues, while Speck and Hoppe (2004) made civic engagement and communitarian involvement primary. Studies have affirmed the long-term positive effects of service-learning programs for students' personal, academic, and moral development (Meyer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ohmer (2007), using cross-sectional data, reports that through serving disadvantaged neighborhoods, volunteers improve their sense of control over personal and community decisions and gain service competency, but he is unable to provide causal evidence for these claims. Meyer et al (2019) did not find that volunteering affects students' general self-efficacy development. Individuals' general self-efficacy is inherently, and by definition, not likely to yield perceptible changes within a short period of volunteering.…”
Section: Hypotheses and Controlsmentioning
confidence: 68%
“…As Bandura (2006) suggests, "The 'one measure fits all' approach usually has limited explanatory and predictive value because most of the items in an allpurpose test may have little or no relevance to the domain of functioning" (p. 307). Addressing this limitation, Meyer et al (2019) suggest that future research should use context-specific self-efficacy measures as our study does.…”
Section: Hypotheses and Controlsmentioning
confidence: 97%
“…There is a large literature on service-learning and the potential positive impact on students personal development and civic engagement. However, many studies into the effects of service-learning programs are unable to disentangle participation effects from selection effects (Meyer et al, 2019). If participation in community-service programs is voluntary, it is very likely that the participating students differ from the non-participating students.…”
Section: Service Learning and Self-selectionmentioning
confidence: 99%
“…Recently, scholars studied the effect of a voluntary community service program at a European university on self-efficacy, generalized trust, empathy and attributions to poverty. Using a pre-post design with a control group, they showed that empathic and trusting students self-selected into the program and that there were no participation effects (Meyer et al, 2019). In addition, females were more likely to participate, while students who were already volunteering were less likely to participate in the community service program.…”
Section: Service Learning and Self-selectionmentioning
confidence: 99%